Indução in vitro de embriões ginogênicos de cebola (Allium cepa L.) a partir de ovários não fecundados - Santos, Cristine Agrine Pereira dos (2022)
Currently, obtaining haploid and double haploid plants in Allium cepa L has been the objective of agricultural companies and also for genetic improvement programs. The use of the induction technique via in vitro cultivation in breeding programs is not a routine practice because there are no efficient methods to regenerate haploids. To carry out the technique, there is a need for protocols for obtaining haploids. Therefore, the general objective of this work was to optimize a protocol through the in vitro culture of flower buds of Allium cepa L. In order to induce gynogenic embryos. The experiments were developed at the UFPB/CCA in the plant biotechnology laboratory. Non-fertilized buds of the variety IPA-11 and BRS Alfa São Francisco were inoculated in BDS, MS and B5 culture medium, with 20 non-fertilized flower buds inoculated in a Petri dish for 120 days. The experiment was conducted in a completely randomized design, in a 32 factorial scheme, the treatments consisted of a combination of doses of 0, 1.0 and 2.0 mg. L-1 of 2,4-D and 0, 1.0 and 2.0 mg. L-1 of BAP, with 7 repetitions each. The variables analyzed were: Induction of bulb formed, number of embryos formed, number of calluses formed, callus diameter, number of leaves, length of main leaf, length of main root, number of callus formed per variety, number of embryos formed per variety, number of albino seedlings formed per variety, percentage of callus per variety, percentage of embryos per variety, percentage of albino plants per variety, percentage of callus formed per treatment and percentage of embryos formed per treatment. Completely randomized, in a factorial 22 scheme, the factorial corresponded to two means Michalik and Adhiyamaan and two varieties of onion IPA 11 and BRS Alfa São Francisco. The variables analyzed by treatments for each variety were: number of callus, number of formed embryos, vitrified buds, viable buds, contaminated plates, percentage of formed callus, number of seedlings. The third experiment consisted of three different culture media B5, BDS and MS, supplemented with 2.0 mg. L-1 of 2.4 D and 2.0 mg. L-1 of BAP, following the same protocols as the others. Previous experiments. In this experiment, the following were evaluated: shoot formation, number of embryos, number of calluses, friable calluses, oxidized calluses, viable buds and vitrified buds. Data were submitted to analysis of variance and when there were significant differences, means were compared using the Scott-Knott test at a 5% probability level. It was observed that the most responsive treatments had 2.0 mg. L-1 of 2,4-D + 2.0 mg. L-1 of BAP in their composition. The BDS culture medium, when supplemented with polyamines, promoted greater efficiency in the induction of gygenic embryos for the IPA 11 variety, as well as showing a greater number of calluses and less oxidation of the explants. As for the media tested for induction, BDS provided a higher percentage of embryos and less callus formation and less callus oxidation, while MS and B5 medium showed a higher rate of oxidized calluses and a smaller number of embryos. Therefore, it can be concluded that the BDS medium supplemented with doses of 2 mg.L-1 of 2.4D and 2.0 mg.L-1 and BAP satisfactorily induce the induction of embryos for both varieties, and when using putrescine and spermidine these frequencies increase for the BRS alto franciscana variety. BDS performs better development in induction. Both experiments perform improvement in onion haploid induction.